Acute Kidney Injury in Pediatric Acute SARS-CoV-2 Infection and Multisystem Inflammatory Syndrome in Children (MIS-C): Is There a Difference? - Grewal, Manpreet K.; Gregory, Melissa J.; Jain, Amrish; Mohammad, Dunya; Cashen, Katherine; Ang, Jocelyn Y.; Thomas, Ronald L.; Valentini, Rudolph P. (Frontiers in Pediatrics, 2021)
Objective: To evaluate the prevalence and factors associated with the risk of acute kidney injury (AKI) in pediatric patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and multisystem inflammatory syndrome in children (MIS-C). Study Design: We performed a retrospective chart review of 113 patients with SARS-CoV-2 infection with or without MIS-C admitted at Children’s Hospital of Michigan (CHM) from March to August 2020. Patient demographic details, laboratory data, imaging studies, echocardiography reports and treatment data were collected. Results: Of the 92 patients included in the final analysis, 22 (24%) developed AKI with 8/22 (36%) developing stage 3 AKI. The prevalence of AKI was much higher in patients with MIS-C 15/28 (54%) versus those with acute SARS-CoV-2 infection 7/64 (11%), (p value < 0.001). Overall, when compared to patients without AKI, patients with AKI were older in age (11 years vs 6.5 years, p value= 0.007), African American (86% vs 58%, p value=0.028), had MIS-C diagnosis (68% vs 19%, p value <0.001), required ICU admission (91% vs 20%, p value <0.001), had cardiac dysfunction (63% vs 16%, p value <0.001), required inotropic support (59% vs 6%, p value <0.001) and had a greater elevation in inflammatory markers. In a multivariate analysis, requirement of inotropes [Odds Ratio (OR)- 22.8, p value <0.001], African American race (OR-8.8, p value 0.023) and MIS-C diagnosis (OR-5.3, p value 0.013) were the most significant predictors for AKI. All patients had recovery of kidney function, and none required kidney replacement therapy. Conclusion: Children with acute SARS-CoV-2 infection and MIS-C are at risk for AKI, with the risk being significantly greater with MIS-C. The pathogenesis of AKI in acute SARS-CoV-2 infection appears to be a combination of both renal hypo-perfusion and direct renal parenchymal damage whereas in MIS-C, the renal injury appears to be predominantly pre-renal from cardiac dysfunction and capillary leak from a hyperinflammatory state. These factors should be considered by clinicians caring for these children with a special focus on renal protective strategies to aid in recovery and prevent additional injury to this high-risk subgroup.